2020
DOI: 10.3389/fimmu.2019.03005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CD6 and PD-1 Identifies Dysfunctional CD8+ T-Cells During Chronic SIV Infection of Rhesus Macaques

Abstract: Effective CD8 + T-cell responses play an important role in determining the course of SIV/HIV viral infection. Here we identified a unique population of dysfunctional CD8 + T-cells in lymphoid tissues and bronchoalveolar lavage (BAL) of rhesus macaques with chronic SIV infection characterized by co-expression of CD6 and PD-1. The frequency of CD6 and PD-1 co-expressing CD8 + T-cells was significantly increased in lymphoid tissues and BAL during chronic SIV infection compared to pre-infection levels. These CD6 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Pulmonary CD4 + T cells from dysbiotic newborns coexpressed T cell immunoglobulin and mucin-domain containing-3 (TIM-3) and lymphocyte activating gene-3 (LAG-3), which are markers linked to T cell exhaustion (fig. S8A) ( 31 , 77 ). The frequency of dysfunctional CD4 + T cells (expressing LAG-3) correlated with disease severity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary CD4 + T cells from dysbiotic newborns coexpressed T cell immunoglobulin and mucin-domain containing-3 (TIM-3) and lymphocyte activating gene-3 (LAG-3), which are markers linked to T cell exhaustion (fig. S8A) ( 31 , 77 ). The frequency of dysfunctional CD4 + T cells (expressing LAG-3) correlated with disease severity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, in SIV-infected macaques, the expression of CD6 by PD-1 + CD8 T cells was associated with a reduced proliferation, cytokine secretion and cytotoxic capacity when compared to their CD6 − counterpart. The frequency of CD6 + PD-1 + CD8 T cells positively correlated with SIV viral load and combined targeting of CD6 and PD-1 effectively restored the CD8 T cell proliferation capacity in vitro , suggesting that CD6 may be a new immunotherapeutic target ( 72 ).…”
Section: Hallmarks Of T Cell Exhaustion In Hiv-1 Infectionmentioning
confidence: 99%
“…[33] BAL T cells show an exhausted phenotype, which is associated with high viral replication, chronic inflammation, and severe depletion of tissueresident CD4+ T cells, driving some of the HIV-1 associated lung complications. [34,35] Interestingly, during chronic HIV-1 infection, T cell profiles and dynamics differ significantly between BAL and blood, suggesting concordant and discordant immune responses in different body sites. [36][37][38][39] Tumor growth during HIV-1-associated pKS in the lung mucosa most likely affects the local immune environment.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of this mucosal site in HIV-1 infected individuals by bronchoscopy revealed that chronic HIV-1 infection causes inflammatory alveolitis by infiltration of T cells from the circulation into the alveolar space [33] . BAL T cells show an exhausted phenotype, which is associated with high viral replication, chronic inflammation, and severe depletion of tissue-resident CD4+ T cells, driving some of the HIV-1 associated lung complications [34,35] . Interestingly, during chronic HIV-1 infection, T cell profiles and dynamics differ significantly between BAL and blood, suggesting concordant and discordant immune responses in different body sites [36–39] .…”
Section: Introductionmentioning
confidence: 99%